2012
DOI: 10.1063/1.3675919
|View full text |Cite
|
Sign up to set email alerts
|

Mg impurity in helium droplets

Abstract: Within the diffusion Monte Carlo approach, we have determined the structure of isotopically pure and mixed helium droplets doped with one magnesium atom. For pure 4 He clusters, our results confirm those of M. Mella et al. [J. Chem. Phys. 123, 054328 (2005)] that the impurity experiences a transition from a surface to a bulk location as the number of helium atoms in the droplet increases. Contrarily, for pure 3 He clusters Mg resides in the bulk of the droplet due to the smaller surface tension of this isotope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…However, because of the weakly attractive long range and strongly repulsive short range interaction of the He atoms, very large basis sets were required in order to get satisfactory results for larger systems. Finally we note that a diffusion Monte Carlo calculation, which has been employed in the past to study both pure and doped 3 He clusters, 43,44,54,55 can be used to study larger clusters up to several tens of atoms. Work along these lines is now in progress.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the weakly attractive long range and strongly repulsive short range interaction of the He atoms, very large basis sets were required in order to get satisfactory results for larger systems. Finally we note that a diffusion Monte Carlo calculation, which has been employed in the past to study both pure and doped 3 He clusters, 43,44,54,55 can be used to study larger clusters up to several tens of atoms. Work along these lines is now in progress.…”
Section: Discussionmentioning
confidence: 99%
“…For alkaline earth atoms, due to their interaction with He, predictions regarding the preferred location, either at the surface or immersed in the bulk, are found to be in principle more uncertain. Mg, for example, constitutes an interesting borderline case between surface location and solvation . Spectra of Ca, Sr, and Ba attached to helium droplets are, conversely, much broader blue‐shifted than those for alkalis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limited tuning range of the laser system excitation spectra could only be recorded for frequencies above 29 600 cm −1 , i.e., in the range where spectra start to overlap. The upper panel of Figure 7 shows the 1+1 excitation spectra of barium attached to helium droplets with a mean radius of 41 Figure 7. In addition, there are two singlet states at slightly lower energies, i.e., 5d6p…”
Section: Excitation Spectrummentioning
confidence: 99%
“…More recent spectroscopic and mass spectrometric experiments have questioned the interior location of the Mg, 35,36 which has sparked intense theoretical effort to determine the location of the alkaline-earth atoms. [37][38][39][40][41] It was theoretically found that while the light alkaline-earth atoms Be and Mg are solvated by the helium, the heavier Ca, Sr, and Ba atoms reside on the surface in a dimple-like structure that is significantly deeper than for the alkali atoms. It is a priori not clear what the effect of the more pronounced dimple structure is on the absorption spectra involving higher excited states or on the dynamics of the excited atoms.…”
Section: Introductionmentioning
confidence: 99%